The Effect of Atopy in the Prevalence of Contact Sensitization: The Experience of a Greek Referral Center - Anna Tagka; George I. Lambrou; Electra Nicolaidou; Stamatios G. Gregoriou; Alexandra Katsarou-Katsari; Dimitrios Rigopoulos (Hindawi Limited, 2020)
Contact dermatitis is a well-known skin condition, which is related to stimuli and environmental exposure to chemicals, affecting all ages as well as both genders. In the present work, we attempt to investigate the patterns of contact sensitization, with respect to the personal history of atopy (AT), in Greece in a large number of allergens, using patch testing. The retrospective analysis included clinical routine data of 1978 patients collected from 2014 to 2016 in the Laboratory of Patch Testing, National Referral Centre of Occupational Dermatoses. Sensitization, in all cases, was tested with 28 allergens of the European baseline series as adjusted to our local circumstances and clinical experience. A total population of 1978 patients was evaluated, with a male-to-female ratio of 0.45 (1359 females/619 males). From our patient cohort, 693 (35%) patients were evaluated with a history of atopy, while 1285 (65%) were nonatopic. The five most prevalent allergens in the total population without AT were nickel sulphate 5% (15.47%), fragrance mix (I) 8% (9.10%), balsam of Peru (6.47%), cobalt chloride 1% (4.70%), and thiomersal 0.1% (4.10%). Respectively, in the total population with AT, the five most prevalent allergens were nickel sulphate 5% (10.36%), fragrance mix (I) 8% (5.11%), balsam of Peru (3.29%), thiomersal 0.1% (3.03%), and cobalt chloride 1% (2.78%). Contact dermatitis surveillance is of great importance towards the clinical and systematic understanding of the disease. Further studies should be directed towards that end, in order to facilitate more effective health policies.